INTRODUCTION TO THE STUDY OF ISLAMIC LAW : al-Madkhal li-Dirasat al-Shari'ah al-Islamiyyah - Yusuf Al-Qaradawi, 1926- , author; Azman Ismail, translator; Md. Habibur Rahman, translator; Ahmad Auzie Mohd. Arshad, translator (Kuala Lumpur : IBFIM, 2013)
Includes bibliographical references and index.